An organic fluorophore-nanodiamond hybrid sensor for photostable imaging and orthogonal, on-demand biosensing. Issue 1 (December 2017) - Purdey, Malcolm; Capon, Patrick; Pullen, Benjamin; Reineck, Philipp; Schwarz, Nisha; Psaltis, Peter; Nicholls, Stephen; Gibson, Brant; Abell, Andrew
Abstract Organic fluorescent probes are widely used to detect key biomolecules; however, they often lack the photostability required for extended intracellular imaging. Here we report a new hybrid nanomaterial (peroxynanosensor, PNS), consisting of an organic fluorescent probe bound to a nanodiamond, that overcomes this limitation to allow concurrent and extended cell-based imaging of the nanodiamond and ratiometric detection of hydrogen peroxide. Far-red fluorescence of the nanodiamond offers continuous monitoring without photobleaching, while the green fluorescence of the organic fluorescent probe attached to the nanodiamond surface detects hydrogen peroxide on demand. PNS detects basal production of hydrogen peroxide within M1 polarised macrophages and does not affect macrophage growth during prolonged co-incubation. This nanosensor can be used for extended bio-imaging not previously possible with an organic fluorescent probe, and is spectrally compatible with both Hoechst 33342 and MitoTracker Orange stains for hyperspectral imaging.